Isolation and characterization of extracts from (Aegiceras floridum) leaves using bioactivity-guided techniques - Lacaden, Mialo Cruz.
Suso does not compete for food with the fishes. The juveniles thrive at the bottom of the ponds. Suso displaces the growing "lablab" complex and the algae where fishes feed from. This greatly affects the fish yield for every harvest time., The study mainly focuses on the feasibility of Aegiceras floridum leaes as a molluscicide. Aegiceras floridum were affirmed to have a molluscicidal activity against Cirithidea cingulata commonly as suso. Toxity bioassay revealed that the crude methanolic , n-hexane and dichloromethane extracts had a lethal dosage, LC50 of 78.47 ug/mL, 53.89ug/mL and 692.7 ug/mL respectively. Qualitative test on the Thin Layer Chromatogram showed the presence of phenols, tannins and flavonoids, higher alcohols, steroids and essential oil. Fourier Transformed Infrared Spectroscopy using Diffuse Reflectance Infrared Fourier Transform Spectroscopy exhibited the presence of alcohol (3600-4000 cm-1) and amides (1500-1700 cm-1).
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Aegiceras floridum